Vasodilatory responses of renal interlobular arteries to epoxyeicosatrienoic acids analog are not enhanced in Ren-2 transgenic hypertensive rats: evidence against a role of direct vascular effects of epoxyeicosatrienoic acids in progression of experimental heart failure - Sporková, A; Husková, Z; Škaroupková, P; Rami Reddy, N; Falck, J R; Sadowski, J; Červenka, L (Physiological research, 2017)
Pathophysiological mechanisms underlying the development of renal dysfunction and progression of congestive heart failure (CHF) remain poorly understood. Recent studies have revealed striking differences in the role of epoxyeicosatrienoic acids (EETs), active products of cytochrome P-450-dependent epoxygenase pathway of arachidonic acid, in the progression of aorto-caval fistula (ACF)-induced CHF between hypertensive Ren-2 renin transgenic rats (TGR) and transgene-negative normotensive Hannover Sprague-Dawley (HanSD) controls. Both ACF TGR and ACF HanSD strains exhibited marked intrarenal EETs deficiency and impairment of renal function, and in both strains chronic pharmacologic inhibition of soluble epoxide hydrolase (sEH) (which normally degrades EETs) normalized EETs levels. However, the treatment improved the survival rate and attenuated renal function impairment in ACF TGR only. Here we aimed to establish if the reported improved renal function and attenuation of progression of CHF in ACF TGR observed after she blockade depends on increased vasodilatory responsiveness of renal resistance arteries to EETs. Therefore, we examined the responses of interlobar arteries from kidneys of ACF TGR and ACF HanSD rats to EET-A, a new stable 14,15-EET analog. We found that the arteries from ACF HanSD kidneys rats exhibited greater vasodilator responses when compared to the ACF TGR arteries. Hence, reduced renal vasodilatory responsiveness cannot be responsible for the lack of beneficial effects of chronic sEH inhibition on the development of renal dysfunction and progression of CHF in ACF HanSD rats.
Keywords: Animals; Kidney; Vasodilation; vztah mezi dávkou a účinkem léčiva; hypertenze; Heart Failure; Renin; acetylcholin; srdeční selhání; noradrenalin; vazodilatace; renální oběh; Rats, Sprague-Dawley; kyselina 8,11,14-eikosatrienová; Dose-Response Relationship, Drug; Hypertension; Male; progrese nemoci; potkani Sprague-Dawley; Renal Circulation; Acetylcholine; Disease Progression; Rats, Transgenic; 8,11,14-Eicosatrienoic Acid; krysa rodu Rattus; zvířata; mužské pohlaví; ledviny; renin; Rats; potkani transgenní; Norepinephrine